ANALYSIS AND DESIGN OF ANDROID APPLICATIONS FOR PROCESSING CUSTOMER DATA IN PRINTING CV. SUMBER REZEKI - Dohare, Meniada; Fauzi, Mohammad; Simanjuntak, Perlindungan (Journal for Technology and Science, 2024)
General Background: CV. Sumber Rezeki, a printing company, currently processes customer orders manually, requiring customers to visit the shop and place orders face-to-face. This method is inefficient and inconvenient for both customers and administrators. Specific Background: There is a growing need for businesses to adopt digital systems to enhance customer service and streamline order processing. CV. Sumber Rezeki’s current system lacks the ability to handle customer data, item lists, and order reports efficiently, resulting in delays and miscommunication. Knowledge Gap: Despite the clear benefits of digital transformation in retail and service sectors, the implementation of such systems in small-to-medium-sized enterprises like CV. Sumber Rezeki has been limited. Aims: The aim of this research is to develop a system that improves customer service by simplifying and digitizing the ordering process, thereby making it faster and more efficient for both customers and the company’s administration. Results: The system design includes features for customer data management, item cataloging, and order tracking through a user-friendly interface. The software development employed a structured approach including system analysis, design, coding, testing (via black-box testing), and ongoing support. Novelty: This study introduces an order management system tailored for a small printing business, enabling customers to place orders remotely and allowing the business to manage these orders in real time. Implications: The implementation of this system increases operational efficiency, reduces face-to-face interaction requirements, and saves time for both customers and staff. Further research is needed to explore scalability and integration with other business processes, such as inventory management and customer feedback mechanisms.